(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2021)
A total of 182 non-typhoid Salmonella enterica (NTS) isolates recovered from patients between 1996 and 2014 were included in the current study focused on class 1 integron detection and its association with multidrug resistance (MDR) phenotype. A high prevalence of isolates displaying MDR and penta-resistance (resistance to ampicillin, chloramphenicol, streptomycin, sulfonamide, tetracycline) phenotypes of clinical significance was revealed. Serotype-specific prevalence of antimicrobial resistance as well as class 1 integrons and inserted variable segments was detected in isolates. The results indicated the limitations of current antimicrobial therapy to control infections caused by MDR isolates of NTS, especially belonging to serotype Typhimurium.